EVALUASI KEBIJAKAN SABILULUNGAN 1000 KAMPUNG KABUPATEN BANDUNG - Anjar Pratama Apriliyanto (Magister Administrasi Publik, FISIP, 2021)
Bandung Regency Government adapted the concept of developing an integrated planning area that utilizes a local base with the spirit of sabilulungan (Sundanese: gotong royong) which tries to integrate various development sectors in one activity called